Potencial antioxidante, mineral, inibitório de enzimas α-amilase e lipoxigenase e composição centesimal de espécies da família Apiaceae - Souza, Krisnanda Kelly Castro de (2016)
Eryngium foetidum L., Eryngium cf. campestre and Coriandrum sativum L. are Apiaceae family vegetable appreciated due to its peculiar flavor and consumed mainly in the north and northeast of Brazil. The vegetables are rich in protein, vitamins, fiber, minerals, total phenolics and other essential bioactives for a balanced health. Nevertheless, many vegetables are falling into disuse by the population, instead of processed foods. The rescue consumption of these species is very important, aiming at their nutritional, therapeutic and antioxidant benefits. In this study, was quantified the levels of total phenolic, flavonoids and dihidroflavonoides by molecular absorption spectrophotometry in the ultraviolet. The total antioxidant capacity was also evaluated using five methodologies of in vitro assays: test Total Antioxidant Capacity (TAC), scavenging of DPPH and ABTS radical, Power Reducing and Power Chelating. It was also evaluated the power inhibitor of α-amylase and lipoxygenase extracts. All species showed significant levels of total phenolics, flavonoids and dihidroflavonoides in its composition. All treatments showed antioxidant activity of 50% except the sheets of E. cf. campestre, C. sativum and bracts of E. foetidum in DPPH and bracts of E. foetidum in ABTS. All treatments also exhibited 50% inhibition activity of the enzyme lipoxygenase.In α-amylase only the leaves of E. cf. campestre and C. sativum showed IC50. It was evaluate the phytochemical composition, aiming to meet the nutritional potential of Apiaceae family vegetables, called unconventional: Eryngium foetidum L., Eryngium cf. campestre; and conventional: Coriandrum sativum L. At the centesimal composition analysis Coriandrum sativum L. presented the highest levels of protein. The leaves of Eryngium foetidum L. exhibited higher values than other species in dietary fiber, while Eryngium cf. campestre detach with superior results in lipids. About the analyzed minerals, the leaves of Eryngium cf. campestre expressed results superior to the other in N, Ca, Mg, S and Cu. The amount of iron highlighted in sheets of E. foetidum, whereas P, K, Mn, Zn and B were most significant on leaves of C. sativum. It was concluded that the levels of total phenolic compounds found in these vegetables, characterize them for its high potential in the antioxidant and inhibition of lipoxygenase and α-amylase enzymes. Their protein and mineral levels classify them as species that can be used as a nutritional source in the preparation of other foods and may their regular consumption bring benefit to human health.